Which mothers wean their babies prematurely from full-breastfeeding? An Australian cohort study - Cooklin, A R; Smith, J; Baxter, Jennifer (My University, 2009)
AIM: To identify the maternal and infant characteristics associated with an early transition from full breastfeeding to complementary or no breastfeeding during the first 2 months of life in a large, representative cohort of Australian infants. METHOD: Multinomial logistic modelling was performed on data for infants with complete breastfeeding and sociodemographic data (N = 4679) including maternal age, education, smoking, employment, pregnancy and birth outcomes. RESULTS: Ninety-one percent of women initiated breastfeeding. Sixty-nine percent of infants were being fully breastfed at 1 month, and 59% were fully breastfed at 2 months. Maternal characteristics - age less than 25 years, smoking in pregnancy, early full-time postnatal employment and less educational attainment - were associated with early breastfeeding cessation. Infant factors - multiple birth, caesarean birth, infant or first birth - were associated with a transition to complementary breastfeeding in the first postnatal month. CONCLUSION: Breastfeeding duration is substantially affected by breastfeeding outcomes in the first postpartum month. The first month is an important window for evidence-based interventions to improve rates of full breastfeeding in groups of women identified as at risk of early breastfeeding cessation.
Acta Paediatrica
Keywords: Health -- Breastfeeding; Health and wellbeing; Health; Breastfeeding; Health and wellbeing